Cervical cancer screening in primary health care setting in Sudan: a comparative study of visual inspection with acetic acid and Pap smear - Ibrahim A; Aro AR; Rasch V; Pukkala E (Dove Medical Press, 2012)
Ahmed Ibrahim1, Arja R Aro1, Vibeke Rasch2, Eero Pukkala3,41Unit for Health Promotion Research, University of Southern Denmark, Esbjerg, Denmark; 2Department of Obstetrics and Gynecology, Odense University Hospital, Odense, Denmark; 3Finnish Cancer Registry, Institute for Statistical and Epidemiological Cancer Research, Helsinki, Finland; 4School of Public Health, University of Tampere, Tampere, FinlandObjective: To determine the feasibility of visual inspection with the use of acetic acid (VIA) as a screening method for cervical cancer, an alternative to the Pap smear used in primary health care setting in Sudan, and to compare sensitivity, specificity, positive and negative predictive values, and histological diagnosis of positive cases of both tests.Methods: A cross-sectional study of 934 asymptomatic women living in Khartoum, Sudan, was conducted during 2009–2010. A semi-structured questionnaire containing socio-economic and reproductive variables was used to collect data from each participant. Methods of screening used were VIA and conventional Pap smear, followed by colposcopy and biopsy for confirmation of the positive results of both screening tests.Results: The tests identified altogether 119 (12.7%) positive women. VIA detected significantly more positive women than Pap smear (7.6% versus 5.1%; P = 0.004), with an overlap between the two screening tests in 19% of positive results. There was no significant difference between VIA and Pap smear findings and sociodemographic and reproductive factors among screened women. Use of colposcopy and biopsy for positive women confirmed that 88/119 (73.9%) were positive for cervical intraepithelial neoplasia. VIA had higher sensitivity than Pap smear (74.2% versus 72.9%; P = 0.05) respectively. Out of 88 confirmed positive cases, 22 (25.0%) cases were invasive cervical cancer in stage 1, of which 19 versus three were detected by VIA and Pap smear respectively (P = 0.001). VIA had higher sensitivity and lower specificity than Pap smear (60.2% versus 47.7%) and (41.9% versus 83.8%) respectively. The combination of VIA/Pap has better sensitivity and specificity than each independent test (82.6% and 92.2%).Conclusion: The findings of this study showed that VIA has higher sensitivity and lower specificity compared to Pap smear, but a combination of both tests has greater sensitivity and specificity than each test independently. It indicates that VIA is useful for screening of cervical cancer in the primary health care setting in Sudan, but positive results need to be confirmed by colposcopy and biopsy.Keywords: cervical, cancer, screening, VIA, Pap smear, colposcopy, sensitivity, specificity, predictive value, primary health care setting